A NATIONAL INVESTIGATION OF SCHOOL PSYCHOLOGY TRAINERS' ATTITUDES AND BELIEFS ABOUT EVIDENCE‐BASED PRACTICES. Issue 3 (March 2017) - Reddy, Linda A.; Forman, Susan G.; Stoiber, Karen C.; Gonzalez, Jorge E.
Abstract : The present investigation examined 460 school psychology trainers' attitudes and beliefs about the conditions for the education and training of evidence‐based practices (i.e., assessments and interventions) in training programs in the United States and Canada using an online survey. Trainer attitudes and beliefs about education and training in evidence‐based practices were measured using a 24‐item five‐point Likert scale. Overall, trainers had positive views of evidence‐based practices, as well as program and organizational support for such training. However, trainers rated the education and training of evidence‐based assessments more favorably than evidence‐based interventions. In general, trainer characteristics nor program accreditation status, model, or type of degree offered were found to influence trainers' perceptions about evidence‐based practices. However, trainers with prior experience teaching evidence‐based intervention courses were found to have more supportive views of evidence‐based assessments and interventions than those without such experience. Implications for future training and school practice are discussed.